Low Investment and Large LDC Debt in the 1980's - Cohen, Daniel (American Economic Review, 1993)
This paper aims at disentangling the correlation between LDC debt and investment in the 1980's. I show that a large debt was not an unconditional predictor of low investment in the 1980's, nor was investment abnormally low, when compared to a "financial-autarky" rate, calculated in the text. I do find, however, that the actual service of the debt crowded out investment. For the rescheduling countries I show that 1 percent of GDP paid abroad reduced domestic investment by 0.3 percent of GDP. This is identical to the correlation between investment and foreign finance observed in the 1960's.